Model Technology-Supported Project-Based Learning Assisted by Gending Rare to Foster Elementary Students’ Global Diversity Character - Delsa Ayu Afianda; I Gusti Agung Ayu Wulandari; Anak Agung Ayu Dewi Sutyaningsih (Journal of Education Technology, 2026)
Global diversity character needs to be strengthened through contextual and culturally meaningful learning in elementary schools. This study aimed to examine the effect of the Project-Based Learning model assisted by the Gending Rare game on the global diversity character of fourth-grade students. This study employed an experimental research design involving two groups: an experimental group taught using Project-Based Learning assisted by the Gending Rare game and a control group taught using conventional learning. Data were collected through a non-test technique using an observation sheet developed based on the global diversity dimension of the Pancasila Student Profile. The data were analyzed using descriptive statistics, assumption tests, and a pooled variance t-test. The results showed that the experimental group achieved a mean percentage of 87.72%, categorized as high, while the control group achieved 77.97%, categorized as sufficient. The pooled variance t-test showed that the t-value of 8.996 exceeded the t-table value of 2.0032 at the 5% significance level. These findings indicate that Project-Based Learning assisted by the Gending Rare game significantly strengthens students’ global diversity character. This model can be used as an innovative alternative for integrating local wisdom into character education.